Pengaruh Pemberian Ekstrak Kulit Manggis (Garcinia Mangostana L.) Dalam Mencegah Peningkatan Kadar Proteinuria Tikus Putih (Rattus Norvegicus) Yang Diinduksi Gentamisin - Asih Anggraini; Ratih Puspita Febrinasari; Nur Hafidha Hikmayani (Nexus Biomedika, 2014)
Background : The increasing use of nephrotoxic drugs has increased the incidence of renal diseases. Research on herbs with potential nephroprotective effects is needed to offer adjuvant therapy for renal diseases. Mangosteen peel contains gamma-mangostin and antioxidant which can prevent renal damages. Methods : This research was a laboratory experiment with pre and post-test control group design. Subjects were 30 white, male, Wistar-strain rats (Rattus norvegicus), aged 2-3 months and weighed 150-230 grams. Subjects were randomly divided into 5 groups. Negative control group was treated nothing, while normal control group was treated 0.5% NaCMC. Treatment group 1, 2 and 3 were treated with mangosteen peel extract at dose 62.5 mg/kg-BW, 125 mg/kg-BW and 250 mg/kg-BW, respectively. The treatment was done for 14 days. In the last 7 days, the negative control group and the treatment groups 1, 2, and 3 were induced by gentamicin 100 mg/kg-BW. Urine samples of the subjects were collected before and after treatment to measure proteinuria levels. Data were analyzed by Kruskal-Wallis test and Mann-Whitney tests (? = 0.05) using SPSS 16.0 for Windows. Results : Result of Kruskal-Wallis test showed that proteinuria levels differed significantly across five groups (p = 0.008). The Mann-Whitney tests showed statistically significant differences between the negative control group and the other 4 groups (p < 0.05). No significant difference was found between the normal control group and the treatment groups 1, 2, and 3 (p > 0.05). Conclusion : Mangosteen (Garcinia mangostana L.) peel extract could prevent the increase of proteinuria levels in white rats (Rattus norvegicus) induced gentamicin. Keywords : Mangosteen Peel Extract, Proteinuria Level, Gentamicin